Transformative metrics for holistic ministry in the marketplace - Lee, Samuel (Missiology, 2019)
Holistic ministry is now the standard across global missional practice, and one manifestation of integral mission is Entrepreneurial Church Planting (ECP). This occurs when business entrepreneurs and clergy members launch spiritually and economically integrated communities of faith. While it may be conceptually inviting for spiritual and business forces to comingle in reaching the lost, ECP activities need to be evaluated as to whether they are accomplishing the goals of the Great Commission and the Creation Commission. In-depth study is needed now to consider outcomes relative to goals. To that end, this study will examine the unique data trends that emerge in the case study of Kentucky-based Meridzo Ministries. Grassroots insights from case-study research will then be applied to Clemens Sedmak's kinship model in order to posit three proxy indicators based upon interviewee data. This article argues that rather than measuring success of missions economically or spiritually, success should be gauged on the grounds of holistic relational transformation.